An examination of house price bubble in the real estate sector: the case of a small island economy – Fiji. Issue 4 (25th February 2021) - Khan, Mohsin; Singh, Rup; Patel, Arvind; Jain, Devendra Kumar
Abstract : Purpose: This paper aims to assess the equilibrium house price in the city of Suva (Fiji) and to analyse the house price bubble in the Fiji housing market. Design/methodology/approach: This paper adopts a time series approach to determine the presence of house price bubbles in Fiji over the period from 1988 to 2018. Findings: The findings suggest that real income, land cost, building material price, inflation rate, volatility, household size and wealth have a positive impact on house prices, whereas user cost of capital and political disturbances have a negative impact. The findings further indicate that the Fijis' housing market does not constitute any house price bubble. Practical implications: This paper draws policy implications for a small developing state (Fiji) and other similar economies. Originality/value: The price bubble in the Fiji housing market is analysed for the first time. This paper develops a comprehensive empirical approach to assess the equilibrium-housing price in Fiji.